Differences in the clinical and genetic profile of Hispanic and non-Hispanic acute myeloid leukemia patients. (February 2019) - Kamath, Geetanjali R.; Tremblay, Douglas; Coltoff, Alexander; Caro, Jessica; Lancman, Guido; Bhalla, Sheena; Najfeld, Vesna; Mascarenhas, John; Taioli, Emanuela
Graphical abstract: